Mineral equilibria constraints on open-system melting and consequences of melt loss in metabasic rocks - Stuck, Tristan James (Department of Geological Sciences, 2017)
Metabasic rocks constitute a significant proportion of the rock types found within orogenic metamorphic terranes, and the high temperature (T), suprasolidus behaviour of these lithologies provide an important contribution to the process of internal differentiation in the continental crust. The recent development of thermodynamic activity-composition (a-x) relations for high T mineral and melt phases allows the processes of melt generation and segregation to be quantified using high-resolution mineral equilibria modelling for the first time. In this work, calculated Pressure-Temperature (P-T) and Temperature-Mol. % SiO₂ (T-MSiO₂) phase diagrams are used to investigate the suprasolidus evolution of representative amphibolite and eclogite compositions under orogenic P-T conditions in the crust.